2011
DOI: 10.2527/jas.2010-2839
|View full text |Cite
|
Sign up to set email alerts
|

Additivity of effects from dietary copper and zinc on growth performance and fecal microbiota of pigs after weaning1,2

Abstract: Four experiments were conducted to determine the interactive effects of pharmacological amounts of Zn from ZnO and Cu from organic (Cu-AA complex; Cu-AA) or inorganic (CuSO(4)) sources on growth performance of weanling pigs. The Cu was fed for 4 (Exp. 1) or 6 (Exp. 2, 3, and 4) wk after weaning, and Zn was fed for 4 (Exp. 1) or 2 (Exp. 2, 3, and 4) wk after weaning. Treatments were replicated with 7 pens of 5 or 6 pigs per pen (19.0 ± 1.4 d of age and 5.8 ± 0.4 kg of BW, Exp. 1), 12 pens of 21 pigs per pen (ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 36 publications
3
33
0
1
Order By: Relevance
“…Administration of Zn and Cu together usually does not cause additive effects, however, Perez et al (2011) observed appearance of additive effect of supplementation with pharmacological amounts of ZnO and CuSO 4 on weaning piglets growth. Shelton et al (2011) have shown advantages of inclusion of Zn and Cu in the pigs diet when Zn was added from 0 to 14 days postweaning and Cu from 14 to 42 days postweaning.…”
Section: Nutritional Interactions Of Zinc/copper With Products Reducimentioning
confidence: 93%
“…Administration of Zn and Cu together usually does not cause additive effects, however, Perez et al (2011) observed appearance of additive effect of supplementation with pharmacological amounts of ZnO and CuSO 4 on weaning piglets growth. Shelton et al (2011) have shown advantages of inclusion of Zn and Cu in the pigs diet when Zn was added from 0 to 14 days postweaning and Cu from 14 to 42 days postweaning.…”
Section: Nutritional Interactions Of Zinc/copper With Products Reducimentioning
confidence: 93%
“…Metals like copper and zinc are mentioned as potential alternatives in the literature too. They have been allowed as a (prescription) medicine in piglet feed in some European Union countries for several years, while in other EU countries is it not tolerated due to legal differences (Smith et al, 1998;Fard et al, 2010;Pérez et al, 2010;Mavromichalis, 2011; European Food Safety Authority (EFSA) panel on Additives Products or Substances used in Animal Feed (FEEDAP), 2012; Center of Expertise on Antimicrobial Consumption and Resistance in Animals (AMCRA), 2014c). Thacker (2013) addresses less traditional alternatives such as rare earth elements, clay minerals, antimicrobial peptides or essential oils and subsequently highlights the inconsistent results and the inferior effectiveness compared to antimicrobial agents of the majority of these compounds.…”
Section: Introductionmentioning
confidence: 98%
“…Use of genetically enhanced, high-resistance breeds or efforts towards eradication of diseases might also play a role in serving as alternatives to high usage of antimicrobial agents in pig production (Grol et al, 1990;Maes et al, 2007;Doeschl-Wilson et al, 2009;Opriessnig et al, 2009;Lunney and Chen, 2010;Pérez et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, although supplementation of both Cu and Zn at levels well above the pig's physiological requirements improve weaned pig performance (Pérez et al, 2011;Shelton et al, 2011), extended supplementation of minerals may lead to poor performance. Yet Kline et al (1972) reported no main or interactive effects of up to 500 mg/kg Cu and up to 300 mg/kg Zn on feed efficiency when fed from 17.3 to 90.8 kg.…”
Section: Discussionmentioning
confidence: 99%